Analysis of the relevance of the information content given to the players during volleyball timeouts with a 3D device. (2nd November 2021) - Lombard, Gilles; Cloes, Marc
ABSTRACT: The timeout in sport is relatively well analysed in the literature. Nevertheless, no study concerns the relevance of the information transmitted to the players. Our study aims to determine the relevance of the content transmitted to the players during volleyball timeouts with a 3D device. We immerged 17 coaches into two sequences of a volleyball game. They had to think aloud during the game and talk directly to the players during the timeouts. Between the sequences, they also had to transcribe and rate all the observations they remembered. By comparing the observations made, the speech during the timeouts and the rating of the coaches' observations, we obtained some interesting results. Few coaches transmitted all the observations considered as the most important to their players during the timeouts, but this selection of the information seemed better in a negative game context. Another result is that the coaches did not seem to be influenced by the short-term memory as the transmitted content rarely corresponded to the last observations made just before the timeout. This study offers perspectives in coaching analysis and education as the 3D device seems to be a tool allowing the study of aspects difficult to attain with other methods.